Hubungan Persepsi dan Motivasi Belajar Siswa terhadap Gaya Mengajar Interaksional Guru Madrasah Aliyah Negeri (MAN Buleleng) di Desa Patas Kecamatan Gerokgak - Rahmat, Dani; Wesnawa, I Gede Astra; Sriartha, I Putu (Universitas Pendidikan Ganesha, 2025)
This study aims to analyze students’ perceptions of teachers’ teaching styles in geography lessons, students’ motivation towards learning geography and the relationship between students’ perceptions and learning motivation towards teachers’ interactional teaching styles. This research uses a quantitative approach with a correlational method. The sample consists of 11th-grade social studies students, determined using the census sampling technique, and data were collected through a Likert scale questionnaire. The data were then analyzed using descriptive analysis techniques. The results show a positive and significant relationship between the teacher's interactional teaching style and students' learning motivation. The teacher's teaching style also proved to make a meaningful contribution to increasing students' learning motivation. It can be concluded that the better the interaction built by the teacher during the learning process, the higher the students' learning motivation. These findings are in line with constructivist theory and Vygotsky's theory, which emphasize the importance of social interaction and contextual learning in improving students' motivation and learning outcomes.